Performance Evaluation of CAMA for Agriculture Domain - Chanda, Jayeeta; Chanda, Sanatnu (INFOCOMP Journal of Computer Science, 2010)
Mobile devices are becoming more and more popular and accessible day by day. In this paper, we propose a context aware middleware architecture (CAMA) that is suitable for use in the agriculture domain. Farmers retrieve context aware information regarding agricultural domain from agriculture databases with the help of mobile devices that have a GUI that display information in vernacular. Our proposed architecture (CAMA) acts as an interface between farmer and database and correctly maps the retrieved data to its vernacular form and vice versa and also ensures uniform abstraction of the database and location data .The middleware maps the data retrieved in English to its vernacular counterpart using the grammar that is defined in the mapping module. We have defined a formal approach to validate the functionality of the mapping module and also present performance analysis for sample query.